2014
DOI: 10.5603/fhc.2014.0025
|View full text |Cite
|
Sign up to set email alerts
|

Renal interstitial mast cell counts differ across classes of proliferative lupus nephritis

Abstract: Systemic lupus erythematosus frequently involves the kidneys leading to significant morbidity and mortality. It is classified according to glomerular involvement pattern but tubulointerstitial lesions are also important for progression and prognosis, as seen in other kidney glomerular diseases. One of the cell types which participate in this process are mast cells. The aim of the study was to analyze the counts of tryptase-positive and chymase-positive mast cells in lupus nephritis classes II, III and IV. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…In our study, more mast cells were seen in MPGN than in LN. In our present and previous studies [26], we have found the same positive correlation with RIV and creatinine level. Hiromura et al examined the number of interstitial mast cells in both MPGN and LN.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, more mast cells were seen in MPGN than in LN. In our present and previous studies [26], we have found the same positive correlation with RIV and creatinine level. Hiromura et al examined the number of interstitial mast cells in both MPGN and LN.…”
Section: Discussionsupporting
confidence: 90%
“…They found a correlation between mast cell count, interstitial fibrosis, creatinine level and leukocyte infiltration, but not with urinary protein excretion; the same results were obtained in our study. In our previous study, we found that mast cell counts differ across classes of SLE, which suggests that these cells play a role in the pathogenesis of LN [26].…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, we confirmed that mast cells contribute to renal tubulointerstitial fibrosis, while the number of mast cells correlates with the renal interstitial volume (RIV) [23,24].…”
Section: Discussionsupporting
confidence: 65%
“…Lupus nephritis (LN) develops in ~50% SLE patients, representing the main cause of morbidity and mortality [1,2]. The significance of self-reacting B-cells in the pathogenesis of LN is supported by a strong causal link between autoantibodies against double stranded DNA (dsDNA) and renal involvement [3,4].…”
Section: Introductionmentioning
confidence: 99%